URGENSI BALIK NAMA TANAH WARISAN DALAM MEWUJUDKAN KEPASTIAN HUKUM DAN PENCEGAHAN KONFLIK DI INDONESIA - Suwito, Suwito; Parji, Parji; Darmawan, Didit; Khayru, Rafadi Khan; Dirgantara, Febrian (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
Land inheritance transfer is an important process in Indonesian agrarian law aimed at providing legal certainty to heirs as the rightful owners of inherited land. This process involves the registration of the transfer of land rights from the deceased to the heirs in accordance with applicable laws and regulations, such as Law No. 5/1960 on the Basic Principles of Agrarian Law (UUPA), Government Regulation No. 24/1997 on Land Registration, and Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency Regulation No. 7/2019. These regulations provide a clear legal basis for the implementation of procedures, including incentives such as the waiver of fees if registration is completed within a specified timeframe. This process provides legal certainty and prevents potential conflicts between heirs or with third parties with an interest in the property. With the transfer of ownership, inherited land that has been officially registered in the name of the heirs can be utilized optimally, both for economic activities and other purposes. However, Implementation in the field still faces challenges, such as low public awareness, limited access to land services in remote areas, and bureaucratic complexity. To overcome these obstacles, strategic measures are needed, such as socializing the procedures for transferring land ownership, strengthening the role of Land Deed Officials (PPAT), digitizing land services, and simplifying administrative procedures. Additionally, the government must expand access to land services through policies like the Comprehensive Systematic Land Registration (PTSL). Collaboration between the government, PPAT, and the community is crucial to ensure the success of this process. With a comprehensive approach, land title transfer for inherited property can maximize legal and social benefits and support better land management.